Economic and social policies of Brunei an empirical analysis - Siddiqui, Shamim A.; Hashim, Abdul A.; Wahid, Abu N. M. (1996)
The discovery of oil in 1929 has been a major political and economic event in the modern history of Brunei Darussalam. After the great oil crunch of the 1973-74 and the subsequent increase in the oil price, the society and economy of Brunei stepped into the threshold of a transformation process. This paper is an attempt to examine and analyze this transformation process. It argues that in the midst of the transition, the prime policy goal of the government of Brunei is to diversify the economy and reduce its absolute dependence on oil and gas. In order to do that, Brunei must be able to encourage the growth and development of the domestic industries without significantly distorting the market mechanism. At the same time, it should be able to attract direct foreign investment in Brunei through the appropriate incentives.
Keywords: Brunei Darussalam -- History -- Economic aspects; Brunei Darussalam -- Social conditions